Essentials of knowledge management - Bergeron, Bryan P. (John Wiley & Sons, Inc., 2003)
Reader-friendly survey of Knowledge Management (KM): a business optimization strategy that identifies, selects, organizes, distills, and packages information essential to the business of a company. Provides best practices in knowledge management, examines enabling technologies, and discusses implementation issues.